2008
DOI: 10.1016/j.bmc.2008.03.074
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, cytostatic and anti-HIV evaluations of the new unsaturated acyclic C-5 pyrimidine nucleoside analogues

Abstract: A series of the novel C-5 alkynyl pyrimidine nucleoside analogues (1-14) in which the sugar moiety was replaced by the conformationally restricted Z- and E-2-butenyl spacer between the phthalimido and pyrimidine ring were synthesized by using Sonogashira cross-coupling reaction. Cytostatic activity evaluation of the novel compounds showed that E-isomers exhibited, in general, better cytostatic activities than the corresponding Z-isomers. E-isomer 14 exhibited the best cytostatic effect against all evaluated ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 25 publications
0
36
0
Order By: Relevance
“…N1-sulfonylcytosine derivatives 3-6 were prepared by the condensation of pyrimidine bases with different sulfonyl chlorides, and then transformed to C5-substituted N1-sulfonylcytosines (8,(12)(13)(14)(15) in moderate to very good yield (up to 65%). Microwave assisted reaction significantly shortened the reaction time and favored formation of Mannich product over numerous possible byproducts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…N1-sulfonylcytosine derivatives 3-6 were prepared by the condensation of pyrimidine bases with different sulfonyl chlorides, and then transformed to C5-substituted N1-sulfonylcytosines (8,(12)(13)(14)(15) in moderate to very good yield (up to 65%). Microwave assisted reaction significantly shortened the reaction time and favored formation of Mannich product over numerous possible byproducts.…”
Section: Discussionmentioning
confidence: 99%
“…It has been known that different C5-substituted pyrimidine nucleosides often display antitumor activity. [14][15][16][17] One of the best known examples is 5-fluorouracil which is widely used in the treatment of cancer. 18 Moreover, it has been found that C5-carbonitrile pyrimidine derivatives modified with heterocyclic amines, like piperazine, piperidine and morpholine, could act as promoters of apoptosis in cancer cells through cyclindependent kinase 9 inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally determined absorbance values were transformed into a cell percentage growth (PG) using the formulas proposed by NIH and described previously. [22] This method directly relies on control cells at the day of assay because it compares the growth of treated cells with the growth of untreated cells in control wells on the same plate. value of 50) for a given cell line, the highest tested concentration is assigned as the default value (in the screening data report that default value is preceded by a ">" sign).…”
Section: Proliferation Assaysmentioning
confidence: 99%
“…The solvent (DMSO) was also tested for eventual inhibitory activity by adjusting its concentration to be the same as in the working concentrations (DMSO concentration never exceeded 0.1%). After 72 h of incubation, the cell growth rate was evaluated by performing the MTT assay: experimentally determined absorbance values were transformed into a cell percentage growth (PG) using the formulas proposed by NIH and described previously [10]. This method directly relies on control of untreated cells at the day of substances addition because it compares the growth of treated cells with the growth of untreated cells in control wells on the same plate-the results are therefore a percentile difference from the calculated expected value.…”
Section: Proliferation Assaysmentioning
confidence: 99%